Quantification of Total Phenolics Content and Their Antioxidant Scavenging Capacity in Selected Herbs Extract - Haron, Normah; Muhammad Bunnori , Noraslinda; Md Zin, Noor Hasniza; Abdul Wahab, Widya; Abdul Halim, Khairul Bariyyah (IIUM Medical Journal Malaysia, 2016)
Introduction: G. procumbens, H. sabdariffa and C. nutans contain potential compounds that lead to the development of drugs and supplements. The quantification of phenolic compound was conducted by analyzing the compounds at 3 different fractions (free, insoluble bound and soluble bound). Thus, the objectives of this research were to determine TPC and antioxidant of the plants in three different extracts. Methods: Three replicates of the medicinal plants were extracted with 80% methanol and hydrolysis with HCl and NaOH. The TPC was determined by using Folin-Ciocalteau reagent while antioxidant radical scavenging capacities were analyzed by using the DPPH assay. Results: Results showed that the TPC of the G. procumbens and C. nutans extracts of the insoluble bound extract had the highest amount of phenolic compounds (15.19 ± 0.25 mg of GAE/g and 6.09+ 0.45 mg gallic acid equivalent GAE/g DW, respectively) as compared to the other fractions (p<0.05). In contrast, H. sabdariffa had the highest TPC value inbound soluble phenolic compound (7.63 + 0.28 mg GAE/g DW) than the other fractions (p<0.05). The antioxidant scavenging capacity of the G. procumbens and C. nutans extracts showed that highest IC50 values in the insoluble bound extract > free > soluble bound extract, whereas the bound soluble of H. sabdariffa showed highest IC50 value > free >bound insoluble phenolic extracts. Conclusions: Strong correlations were found between TPC with antioxidant radical scavenging capacity. This finding proved that these three plants could be a good source of natural antioxidant for food, cosmetic and pharmaceutical industry.